Clinical Monitoring of Early Caries Lesions using Cross Polarization Optical Coherence Tomography - Fried, Daniel (2013)
New methods are needed for the nondestructive measurement of tooth demineralization and remineralization and to monitor the progression of incipient caries lesions (tooth decay) for effective nonsurgical intervention and to evaluate the performance of anti-caries treatments such as chemical treatments or laser irradiation. Studies have shown that optical coherence tomography (OCT) has great potential to fulfill this role, since it can be used to measure the depth and severity of early lesions with an axial resolution exceeding 10-μm. It is easy to apply in vivo and it can be used to image the convoluted topography of tooth occlusal surfaces. In this paper we present early results from two clinical studies underway to measure the effect of fluoride intervention on early lesions. CP-OCT was used to monitor early lesions on enamel and root surfaces before and after intervention with fluoride varnish. The lesion depth and internal structure were resolved for all the lesions examined and some lesions had well defined surface zones of lower reflectivity that may be indicative of arrested lesions. Changes were also noted in the structure of some of the lesions after fluoride intervention.